Doping of silicon by phosphorus end-terminated polymers: drive-in and activation of dopants. Issue 30 (27th May 2020) - Perego, Michele; Caruso, Francesco; Seguini, Gabriele; Arduca, Elisa; Mantovan, Roberto; Sparnacci, Katia; Laus, Michele
Abstract : An effective doping technology for precise control of P atom injection and activation into a semiconductor substrate is presented. Abstract : An effective doping technology for the precise control of P atom injection and activation into a semiconductor substrate is presented. Polystyrene polymers with a narrow molecular weight distribution and end-terminated with a P containing moiety are used to build up a phosphorus δ-layer to be used as the dopant source. P atoms are efficiently injected into the Si substrate by high temperature (900–1250 °C) thermal treatments. Temperature dependent (100–300 K) resistivity and Hall measurements in the van der Pauw configuration demonstrate high activation rates ( η a > 80%) of injected P atoms. This bottom-up approach holds promise for the development of a mild technology for efficient doping of semiconductors.